ANEMONE Global's First eDNA ‐Based Assessment: Insights Toward a Standardized Global Monitoring Network - Imane Sioud; Yuki Minegishi; Tadashi Kajita; Yukinobu Isowa; Akifumi S. Tanabe; Hisashi Yamakawa; Oliver Berry; Mohammad Basyuni; Hong-Leong Cheah; Bruce E. Deagle; Jean Pierre Yvon Fall; KA Habib; et al. (Environmental DNA, 2026)
ABSTRACT Environmental DNA (eDNA) enables sensitive detection of species from environmental samples, particularly water. Large‐scale, standardized monitoring of coastal fish communities remains challenging across diverse regions. The ANEMONE Global network was established to address this gap, expanding the workflow developed in Japan to a coordinated worldwide survey using standardized eDNA metabarcoding. Between June and November 2024, 12 countries, including several in Southeast Asia, collected surface water samples from beaches, rocky shores, estuaries, and near coastal protective structures using harmonized protocols for filtration, RNAlater preservation, and metadata recording. Daytime and nighttime sampling captured temporal variation in community composition. All samples were processed with the MiFish metabarcoding protocol, quantitative internal standards, and rigorous contamination controls. Analysis of 90 samples generated over 16.6 million high‐quality reads, revealing more than 500 putative fish OTUs across diverse families, genera, and species. Species richness varied geographically, reflecting differences in fish fauna, and assemblages differed across the Atlantic, Indian, North Pacific, and South Pacific Oceans. Diel variation was most pronounced in the North Pacific, and diversity patterns reflected both habitat complexity and ocean basin, with waters adjacent to coastal protective structures and rocky shores supporting the highest diversity. These findings highlight how both habitat complexity and ocean basin geography shape coastal fish assemblages, offering insights for global marine biodiversity monitoring using eDNA. This survey demonstrates that a globally standardized eDNA workflow can generate comparable quality data across ecological and logistical contexts. By combining international collaboration, open data, and locally informed implementation, ANEMONE Global provides a framework for long‐term, high‐resolution monitoring of coastal biodiversity and sets the stage for expanding coverage to additional aquatic ecosystems worldwide.
Keywords: Environmental DNA in Biodiversity Studies; Genomics and Phylogenetic Studies; Protist diversity and phylogeny